Pharmacoeconomic implications generated by primary open-angle glaucoma on workers - Velkovski, Zoran; Belevska, Maja; Dastevska, Emilija (Acta medicae Medianae, 2021)
Glaucoma is an optic neuropathy which due to the irreversible loss of visual acuity, the direct and consequential costs associated with the treatment and the indirect losses because of the reduced productivity generates social and pharmacoeconomic burdens. The study is designed to assess pharmacoeconomic implications generated by primary open-angle glaucoma on workers. It is a cross sectional study, which includes 190 male and female respondents with primary glaucoma, aged 28-67, with visual acuity >6/18 (0,33), according to the ICD-10 classification, conducted in the period August-November 2020 in North Macedonia. 34,21% of the respondents received low income, 40,53% average and 25,26%, high income. Pharmacological costs for treatment of binocular glaucoma amount to 24,1-45,4 Euros per month, which account for 10,26-19,32% of the respondents’ low income and <4,82-9,08% of the respondents’ high income. In 21,05% the economic burden resulted in existential crisis for the family and 25,79% of the respondents were treated inadequately with generic alternative medicine or inadequate doses of medication due to financial reasons. Loss of productivity was registered in 25,79% of the respondents, while 21,58% of whom, due to their inability to carry out the essential work duties, received lower monthly income. Glaucoma generates a huge pharmacoeconomic burden, which is a consequence of direct and other medical costs for treatment and indirect losses from productivity, which requires the use of screening programs for timely diagnosis and adequate regular treatment, which will help maintain visual acuity and work ability, thus reducing the pharmacoeconomic burden.